DEVELOPMENT OF QUR'AN AND HADITH-BASED MATHEMATICS MODULE FOR STUDENTS' MATHEMATICAL UNDERSTANDING AND RELIGIOUS CHARACTER - Choirudin Choirudin; Agus Setiawan; M. Saidun Anwar; Eka Riyana; M. Sayyidul Abrori; Wahyudi Wahyudi (Universitas Islam Negeri (UIN) Mataram, 2021)
The module is a means of delivering material to students and a supporting tool in the learning process. The teaching materials used are also expected to be able to build the values ??and morality of each student through learning the integration of science and religion, one of which is by using teaching materials based on the Qur'an and Hadith. This study aims to develop teaching materials in mathematics learning in the form of modules based on the Qur'an and Hadith. This type of research is research and development using the Borg & Gall development model. The development of the module is carried out on the fractional number material for class VII Islamic Junior High School (MTs). The data collection instruments used in this study were a questionnaire from media experts, material experts, and religious experts who were used to test the quality of the mathematics module based on the Qur'an and Hadith, as well as a questionnaire response from educators and students who were used to test interest in the developed module. Data collection methods used in this study are interviews, documentation, and questionnaires. This research produces a product in the form of a mathematical module based on the Qur'an and Hadith. In learning using a mathematics module based on the Qur'an and Hadith in grade VII Takhasus MTs Hidayatul Mubtadiin Dayamurni can improve students' mathematical understanding at a moderate level. Learning using a mathematics module based on the Qur'an and Hadith can shape students' religious attitudes.